2022
DOI: 10.1038/s41598-022-24758-6
|View full text |Cite
|
Sign up to set email alerts
|

Frequency control of the islanded microgrid including energy storage using soft computing

Abstract: Today, with the increasing penetration of microgrids, the degree of complexity and non-linearity of power systems has increased, causing conventional and inflexible controllers not to perform well in a wide range of operating points. In this paper, a self-tuning proportional-integral (PI)-controller based on a soft computation of a combination of genetic algorithm (GA) and artificial neural network (ANN). The GA-ANN is used to control the frequency of a microgrid in an island mode to automatically adjust and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Indeed, within a microgrid, it is important to maintain stable frequency, voltage, and power sharing and also to ensure a gain in terms of cost. Thus, the hierarchical structure is constituted of three levels of control to ensure the above objectives [42,84].…”
Section: Hierarchical Control Of the Microgridmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, within a microgrid, it is important to maintain stable frequency, voltage, and power sharing and also to ensure a gain in terms of cost. Thus, the hierarchical structure is constituted of three levels of control to ensure the above objectives [42,84].…”
Section: Hierarchical Control Of the Microgridmentioning
confidence: 99%
“…The ANN approach is applied in [42] in combination with the Genetic Algorithm (GA) to determine the parameters of a PI controller, to control the frequency in an island microgrid. In [43] an adaptive proportional integral (API) controller is replaced by an adaptive neural network (NN) controller to reduce the error signal and cover the frequency uctuations.…”
Section: Arti Cial Neural Network (Ann)mentioning
confidence: 99%
See 2 more Smart Citations
“…These studies are associated with multifunctional devices that can perform tasks such as energy storage, communication, and sensing. An increasing number of studies are exploring the potential of MQW III-nitride diodes. There are few storage interfaces that achieve great function and low cost. The development of next-generation memory urgently needs to overcome the constraints of electrical transmission and realize a faster and less interference transmission scheme, and in this regard, the touchless optical I/O interface is a new scheme. , Oh et al reported a double heterojunction nanorod device that can be used for simultaneous light emission and detection. Using a dual-functional perovskite diode, Shan et al proposed a bidirectional optical link between two identical devices.…”
Section: Introductionmentioning
confidence: 99%